2024
DOI: 10.1001/jamainternmed.2023.7410
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Trends in Complexity of Hospital Inpatients

Hiten Naik,
Tyler M. Murray,
Mayesha Khan
et al.

Abstract: ImportanceClinical experience suggests that hospital inpatients have become more complex over time, but few studies have evaluated this impression.ObjectiveTo assess whether there has been an increase in measures of hospital inpatient complexity over a 15-year period.Design, Setting and ParticipantsThis cohort study used population-based administrative health data from nonelective hospitalizations from April 1, 2002, to January 31, 2017, to describe trends in the complexity of inpatients in British Columbia, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 65 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…The higher comorbidity over time found in the present study is in agreement with results from a large recent Canadian cohort study of 3.4 million hospital admissions reporting an increase in hospital inpatient complexity between 2002 and 2017 10 . One explanation could be active changes in healthcare policy, where smaller non-academic centres manage younger and healthier patients, whereas university hospitals focus more on complex cases with higher comorbidity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher comorbidity over time found in the present study is in agreement with results from a large recent Canadian cohort study of 3.4 million hospital admissions reporting an increase in hospital inpatient complexity between 2002 and 2017 10 . One explanation could be active changes in healthcare policy, where smaller non-academic centres manage younger and healthier patients, whereas university hospitals focus more on complex cases with higher comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Elderly patients have higher rates of major perioperative complications and mortality after non-cardiac surgery, as well as longer hospital stays 7 , 8 . Investigating changes in demography and mortality over time in large, unselected patient populations is unusual 9 , 10 , but in a study of emergency surgery in Scotland over a 20-year period (1996–2015), no significant changes in median age were found 11 . In contrast, a study of the surgical population 2000–2014 in England showed that patients were getting older 12 .…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence of the increasing complexity of hospitalized and surgical patients [7]. It can be hypothesized that this complexity is also associated with anemia and coagulopathy as increasingly encountered comorbid conditions, especially in surgical patients.…”
Section: Aimmentioning
confidence: 99%
“…The generalisability of prediction models refers to their performance in patient groups or healthcare settings other than the one used for training. Variations of patient biographies according to geography and era as well as differences in cultural norms and practice patterns affect care processes and outcomes [4,[42][43][44], especially in very old patients with complex conditions. Thus, the generalisability of many prediction models is limited [45,46] and the performance of these models was shown to degrade when deployed in different healthcare settings or during different periods in time [47,48].…”
Section: Predictive Modellingmentioning
confidence: 99%